Ewing Sarcoma of Orbit with Intracranial Extension - Alyscia Cheema, Sabeen Abbasi (Pakistan Journal of Ophthalmology, 2015)
Ewing sarcoma causing unilateral proptosis in a child is unusual presentation. A young girl presented with painless proptosis of left eye with restricted eye movements. Her radiology revealed a large soft tissue mass causing destruction of lateral orbital wall and zygomatic arch measuring 2.0 × 3.0 cm. Total excision of intracranial and intra orbital part of the tumor brought about substantial relief. The clinical and radiological presentation and management of this entity are discussed. Key words: Sphenoid bone, Ewing sarcoma, orbital proptosis, primitive neuroepithelial tumor (PNET), radiology, small round cell tumor, surgery.